Towards Cloud of Things from Internet of Things - Vaishnavi, D.; Rahman, Shawon; Ramalingam, D. (International Journal of Engineering and Technology, 2018)
The techniques Internet of things (IoT) and Cloud Computing (CC) are becoming a part of our day-to-day life; where IoT connects a billion numbers of devices to share the information by communicating each other and CC grants convenient, on-demand scalable network access in order to utilize the computing resources and it facilitates dynamic data integration from diverse sources. Both techniques are having their own pros and cons. So, a novel paradigm called cloud of things (CoT) is modeled by integrating the both CC and IoT, which enables a large number of applications to get advantages of IoT as well as CC. This paper delivers the basics of the technologies, motivations to model the cloud of things and its benefits. Also, it discusses the implementation challenges.Â Â